Leadership communication : how leaders communicate and how communicators lead in today's global enterprise - Harrison, E. Bruce. (2014 digital library., 2014)
The quality of leadership in any organization--business, social, military, and government--is enhanced or limited by the quality of its leadership communication. The authors of this book, both of whom are experienced in the practice and study of enterprise communication, assert that leadership is given force by strategic communication that produces results required in competitive conditions. For the professional in enterprise communication, this brings into focus two questions: (1) What is the relevance of communication in the leadership process of reaching best achievable outcomes (BAOs)? and (2) How does the primary communication professional attain expert influence and success in a leadership position? This book provides insights and guidance on functioning at the highest levels of the corporate communications profession. This function by an individual identified in many companies as the chief communication officer (CCO) has risen in importance in free-enterprise economies, coincident with the evolution of social media, journalism, data analytics, government engagement, change management, and other factors shaping enterprise strategies and success. The book examines the enterprise CCO at three levels: the communicator rising toward, or newly positioned in responsibility for, enterprise communication; the CCO as a collaborator in leadership with others (chief executive and chief financial officer are examples of those with whom leadership communication is structured and driven); and the developed, influential communication chief dealing with missions, strategies, and the execution of enterprise vision. A detailed guidance is given on information flow that takes advantage of stakeholder perception management and the productive, enabled employee culture. Crisis communication in modern contexts is explained, with emphasis on precrisis intelligence gathering through social conversation analysis, and procedures for crisis communication management are drawn from cases provided by CCOs in author interviews and lectures in the authors' graduate classes at Georgetown University.